A study on the influence of oil film lubrication to the strength of engine connecting rod components. (May 2016) - Zhu, Jun-chao; Zhu, Han-hua; Fan, Shi-dong; Xue, Liang-jun; Li, You-feng
Abstract: Dynamic lubrication analysis of connecting rod is a very complex problem. Some factors have great effect on lubrication, such as clearance, oil viscosity, oil supplying hole and surface roughness. This work establishes the EHD characteristic of bearing and bush to analyze the peak oil film pressure, min oil film thickness and node force with consideration of deformation and cavitation; then create connecting rod components to calculate the stress distribution with consideration of film lubrication or not and finally contract the results of two conditions. The results show that the stress distribution of two conditions is different in individual positions, but the stress calculation method considering the oil film lubrication is more consistent with the actual working conditions. Highlights: For connecting rod stress calculation, this paper considered the effect of oil film lubrication, calculate the oil force and apply it into bearing and bush. Finally analyze the influence of oil lubrication to connecting rod component strength. It is more close to actual operation condition. This paper considers the effect of cavitation in oil film lubrication mathematical calculation. The oil film was divided into full film area and cavitation area. Into order to verify the correctness of calculation method, contracting the results with real condition and other author's research.